Pendidikan Pranatal Menurut Prespektif Islam - Aminullah, Aminullah; Nurhayati, R; Al Amin; Ningsih, Diarti Andra (Al-Qalam: Jurnal Kajian Islam dan Pendidikan, 2023)
This article examines prenatal education in the perfective of Islamic education, Prenatal education is an aspect of education that is less in demand, either in the form of studies or applications in the form of educational institutions oriented to prenatal education. Several studies have been found that prove that the baby in the womb has been able to respond to events related to their biological mother, this is described in the Qur'an QS Al Mukminun: 12, between the baby in the womb and the mother there is a strong bond, Qararin Makin. Humans are creatures who have the basic character of Alaqiyah, have the dependence of QS Al Alaq 2. More firmly, the Qur'an states that the best fetal seedbed is in the garden, which the Qur'an calls the wife is the garden where the best fetus play QS Albaqarah 223 On that basis, the child in the womb can be educated. The one who plays a very important role in the mahluq who loves the child in the womb is his mother assisted by his father. Broadly speaking, there are two ways to educate children in the womb, namely: 1) Supplying nutritious (good) and halal food to babies through their mothers so that children in the womb can develop into healthy and intelligent. 2) His mother and father, even those around him must behave well and avoid bad deeds, so that children can develop into pious children according to their nature.